MOOD AND MODALITY IN JAMES RICE’S NOVEL ALICE AND THE FLY - Aini, Suci Angger; Siwi, Purwanto (Universitas Islam Sumatera Utara, 2025)
This study analyzes the realization of mood and modality in Detective Sergeant Terrence’s dialogues using Halliday’s Systemic Functional Linguistics (SFL) framework. This study aims to analyze mood structure, mood types, and modality contained in detective Sergent Terrence. Alice and the Fly novel by James Rice is about Greg who has Schizophrenia. He falls in love and becomes obsessed. He killed the girl he liked. So detective Sergent Terrence must find out what really happened to him. The data used in this study were from the Alice and the Fly novel by James Rice. This study was written using a descriptive qualitative method. The steps to analyze the data were starting from specifying the data based on the categories that I would analyze. From the result of this study, it can be concluded that the detective uses the mood structure of a finite subject when he communicates with the five characters. Then the use of the interrogative shows the detective wants to know more information about the murder case rather than stating or ordering something. In modality analysis through the use of a modal finite operator and mood adjunct, the results show that the detective tends to use a modal finite operator with low value.